Improving Environmental Health Awareness through the PHAST Method for Household Sanitation Intervention in the Belawan Coastal Region - Evi Naria; Indra Chahaya; Rusmalawaty Rusmalawaty; Diza Fathamira Hamzah; Anggraini Anggraini; Tamia Sakinah Adjani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Coastal areas are often faced with complex public health challenges due to environmental vulnerability and limited access to sanitation facilities. Poor sanitation contributes to a high prevalence of environment-related diseases such as diarrhea and malnutrition among children under five. This quasi-experimental study included 30 households with toddlers in Medan Belawan, Medan City. The Participatory Hygiene and Sanitation Transformation (PHAST) method was implemented to empower families in managing sanitation and hygiene practices. Data were collected through observation and assessment of household sanitation conditions before and after the intervention. Analysis was conducted using the Wilcoxon Signed Rank test at a 95% confidence interval due to non-normal data distribution. The results showed a significant improvement in household sanitation scores after the PHAST intervention (Z = -3.905; p < 0.05). Approximately 63.3% of households had increased scores, particularly in handwashing at critical times, waste management, as well as water and food storage practices, signifying a meaningful magnitude of behavioral change. However, this study was limited by its small sample size, absence of a control group, and short observation period, which hindered causal inference and generalizability. Despite the limitations, the evidences suggest that PHAST is a promising method for improving household sanitation management and hygiene behavior in coastal settings. Future studies with larger samples and controlled designs are recommended to assess sustainability and long-term health outcomes Keywords: Household Sanitation, Environmental Diseases, Coastal Area, PHAST